L’antiféminisme de gauche – un syndrome révisionniste - Dixon, Marlene (Revue PréfiX, 2024)
Même si la misogynie et les agressions sexuelles sont des problèmes bien connus et depuis longtemps dénoncés par des féministes militant dans les réseaux de gauche et d’extrême-gauche, les textes d’analyse sur l’antiféminisme de gauche restent relativement rares dans la vaste production d’études sur l’antiféminisme en général
Keywords: 1800-1899; 1900-1999; amériques; antiféminisme; approches et analyses; capitalisme; communisme; cours; discipline; droits des femmes*; féminisme matérialiste; gauche; patriarcat; pol5185; premier cycle; prolétariat; préFiX; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; traduction; travail; violences; états-unis

Gender, climate breakdown and resistance: The future of human rights in the shadow of authoritarianism - Rosamond, Annika B.; Davitti, Daria (Nordic Journal of Human Rights, 2022)
In this article we examine the future of human rights by looking at how ‘authoritarianism’, in its multifaceted forms and manifestations, intersects with existing discourses on climate change, environmental protection, populism and ‘gender deviance’. By adopting an intersectional lens, we interrogate the emergence of the right to a healthy environment and reflect on whether it will help against the double challenge faced by human rights: of climate breakdown and rising authoritarianism. We study the link between authoritarianism and populism, focusing on far-right populism and the creeping authoritarian features that we can associate with far-right groups, both movements and parties. We also consider how certain understandings of nature and the environment are put forward by authoritarian regimes. This leads us to consider so-called ‘ecologism’ and the ways in which far-right movements draw upon green thought on the natural environment to further a gendered agenda based on conceptions of nature as a ‘national treasure’. These conceptions, as we demonstrate, go hand in hand with policies that promote national identity and directly undermine the rights of migrants, ethnic minorities, women and LGBT+ groups. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; capitalisme; changements climatiques; discipline; droits des femmes*; droits humains; environnement; histoire et politique; intersectionnalité; patriarcat; populisme de droite; projet charge mentale; périodes historiques; racisme; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; écologisme d'extrême-droite